The Relationship Between Teachers’ Perceptions Towards Professional Learning Communities and Their Collective Efficacy at Deqin Middle School in Yunnan Province, China - Liu, Hao; Ye, Yan (Scholar: Human Sciences, 2021)
The main purpose of this study was to determine the relationship between teachers’ perceptions towards professional learning communities and their collective efficacy in Deqin Middle school. The study firstly evaluated teachers’ perceptions of the professional learning communities, examined their collective efficacy, and finally determined the relationship between the professional learning community and collective efficacy. This study used a questionnaire to determine the research objectives, adopted the Professional Learning Communities Assessment-Revised (PLCA-R) created by (Olivier, 2010) and the Collective Efficacy Scale (short form) by Goddard, (2002). The study surveyed 112 full-time teachers in Deqin Middle School in the 2020 academic year. The researchers used the Mean and Standard Deviation to analyze teachers’ perceptions of professional learning communities and their level of collective efficacy. The Pearson Product Moment Correlation Coefficient is used to test the relationship between two variables. The findings indicated that teachers’ perceptions of the professional learning community and their collective efficacy were at a high level. Results of the Pearson correlation indicated that there was a significant relationship between teachers’ perceptions towards professional learning community and their collective efficacy, (r (105) = .583, p = .000).